Age-related changes in European Portuguese vowel acoustics - Albuquerque, Luciana (2020)
This study addresses effects of age and gender on acoustics of European Portuguese oral vowels, given to the fact of conflicting findings reported in prior research. Fundamental frequency (F0), formant frequencies (F1 and F2) and duration of vowels produced by a group of 113 adults, aged between 35 and 97 years old, were measured. Vowel space area (VSA) according to gender and age was also analysed. The results revealed that the most consistent age-related effect was an increase in vowel duration in both genders. F0 decreases above [50-64] for female and for male data suggests a slight drop over the age range [35- 64] and then an increase in an older age. That is, F0 tends to be closer between genders as age increases. In general, there is no evidence that F1 and F2 frequencies were lowering as age increased. Furthermore, there were no changes to VSA with ageing. These results provide a base of information to establish vowel acoustics normal patterns of ageing among Portuguese adults.